2008
DOI: 10.1007/s11060-008-9693-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase II clinical trial of poly-ICLC with radiation for adult patients with newly diagnosed supratentorial glioblastoma: a North American Brain Tumor Consortium (NABTC01-05)

Abstract: Purpose This phase II study was designed to determine the overall survival time of adults with supratentorial glioblastoma treated with the immune modulator, polyinosinic-polycytidylic acid stabilized with polylysine and carboxymethylcellulose (poly-ICLC), in combination with and following radiation therapy (RT). Methods and Materials This was an open-label, single arm phase II study. Patients were treated with RT in combination with poly-ICLC followed by poly-ICLC as a single agent. Poly-ICLC was initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 38 publications
0
73
0
Order By: Relevance
“…Two phase 2 studies with poly ICLC suggested survival advantage awaiting further confirmation [45,46].…”
Section: Vaccination and Immunomodulation For Malignant Gliomasmentioning
confidence: 99%
“…Two phase 2 studies with poly ICLC suggested survival advantage awaiting further confirmation [45,46].…”
Section: Vaccination and Immunomodulation For Malignant Gliomasmentioning
confidence: 99%
“…Antitumor response was associated with activation of 2′5′-oligoadenylate synthetases, which are antiviral proteins induced by type I IFN [ 143 ]. In another study, 30 adult patients with glioblastoma multiforme received poly-ICLC in combination with radiotherapy, thereby demonstrating an advantage in relation to historical studies using radiotherapy alone [ 144 ]. Okada's group is currently analyzing the effect of associating poly-ICLC with DC vaccines generated under INF−α(αDC1), previously shown to be more effective than conventional DCs at inducing an antigen-specifi c CTL response [ 145 ].…”
Section: Vaccine For Nervousmentioning
confidence: 99%
“…Poly-ICLC is also used in combination with radiotherapy for low-grade recurrent B and T cell lymphoma, and for brain and central nervous system tumors in phase I and II clinical phase. Interestingly, a phase II clinical trial from the North American Brain Tumor Consortium for 30 patients with newly diagnosed supratentorial glioblastoma showed that treatment with radiotherapy in combination with Poly-ICLC followed by Poly-ICLC as a single agent was relatively well-tolerated and enhanced the survival of patients compared to historical studies using radiotherapy alone [95]. Then, the New Approaches to Brain Tumor Therapy (NABTT) consortium assigned 365 patients with newly diagnosed glioblastoma in phase II clinical trial for testing novel agents in combination with radiation + temozolomide and compared the results with the data from the European Organization for Research and Treatment of Cancer (EORTC) phase II study [96,97].…”
Section: Dsrna In Clinical Trialsmentioning
confidence: 99%